KEMUDAHAN PENGGUNAAN SISTEM SEBAGAI PEMODERASI PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA KINERJA - Mercika, Ni Luh Dewi Tresna; Jati, I Ketut (E-Jurnal Akuntansi, 2015)
The goal of this study to demonstrate the effectiveness of accounting information system’s impact on the employee performance with the ease of use of the system as a moderating variable in PT. BPR Sri Artha Lestari Denpasar. Sample size of 82 employees who were taken by purposive sampling technique. This research used multiple linear regression and Moderated Regression Analysis (MRA) as analysis technique to test hypotheses. The study found that the effectiveness of Accounting Information Systems ( AIS ) and the ease of use of the system had significant positive reaction on employee performance. But the ease of use of the system had a value that was not significant at the relationship between the effectiveness of AIS with the performance of employees, so the ease of use of the system instead of moderating variables.
Keywords: system ease of use, effectiveness of AIS, employee performance